A Pooling Genome-Wide Association Study Identifies Susceptibility Loci and Signaling Pathways of Immune Thrombocytopenia in Chinese Han Population. (11th March 2020) - Xu, Yanmei; Li, Jing; Yang, Wentao; Tang, Xiaoli; Huang, Bo; Liu, Jing; Lin, Jin; Zhang, Jing; Yang, Weiming; Li, Shuqi; Sun, Fan; Deng, Libin; et al.
Abstract : Immune thrombocytopenia (ITP) is an acquired bleeding disease due to immune-mediated destruction of antilogous platelets and ineffective thrombopoiesis. Although the etiology of ITP remains unknown, genetic variants are thought to predispose individuals to the disease. Several candidate gene analyses have identified several loci that increased ITP susceptibility, but no systematic genetic analysis on a genome-wide scope. To extend the genetic evidence and to identify novel candidates of ITP, we performed a pooling genome-wide association study (GWAS) by IlluminaHumanOmniZhongHua-8 combining pathway analysis in 200 ITP cases and 200 controls from Chinese Han population (CHP). The results revealed that 4 novel loci (rs117503120, rs5998634, rs4483616, and rs16866133) were strongly associated with ITP (P < 1.0 × 10 − 7 ). Expect for rs4483616, other three loci were validated by the TaqMan probe genotyping assay (P < 0.05 ) in another cohort including 250 ITP cases and 250 controls. And rs5998634 T allele was more sensitive to glucocorticoids for ITP patients (χ 2 = 7.30, P < 0.05 ). Moreover, we identified three overrepresented signaling pathways including the neuroactive ligand-receptor interaction, pathways in cancer, and the JAK-STAT pathway, which involved in the etiology of ITP. In conclusion, our results revealed four novel loci and three pathways related to ITP and provided new clues to explore the pathogenesis of ITP.